The multidimensional effects of extensive listening on EFL learners - Chang, Anna C-S; Renandya, Willy Ardian (Journal of Research on English and Language Learning (J-REaLL), 2024)
This study investigated the multidimensional effects of extensive listening (EL) on learners’ actual language gains, selection of study materials, and practice styles. Language gains were measured through a pre- and a post-test on students’ aural vocabulary test (Listening Vocabulary Levels Test, LVLT) and general listening comprehension (TOEIC), administered before and after the intervention. Fifty-five university student participants took part in the four-month experiment; they were entirely free to select their favorite study materials online or off-line. The results showed that each student spent an average of 1,387 minutes (approximately 87 minutes per week) doing EL practice. The three most popular study materials were the following: Songs (63.64%), movies (49.09%), and talks (43.46%); materials were mainly from YouTube (74.55%), Netflix (49.09%), and other miscellaneous sources (43.63%). Their practice style was unanimously a combination of viewing and listening. From the pre-tests to the post-tests, students made significant gains in both LVLT and TOEIC, but the effect sizes were small. Some suggestions are made for implementing EL.